QELBY®-Induced Enhancement of Exclusion Zone Buildup and Seed Germination. (1st March 2017) - Sharma, Abha; Toso, Dario; Kung, Kurt; Bahng, Gun-Woong; Pollack, Gerald H.
Abstract : A hydrophilic powder, QELBY, from the feldspar family of clay minerals was investigated for its ability to form structured or exclusion-zone (EZ) water. We demonstrated microsphere-free zones around different fractions of the QELBY powder or its hydrated pellet. Averaging approximately 100 μ m, these zones grew to a size similar to that formed in the vicinity of the Nafion standard. In the case of silica (control), only occasional microsphere-free zones of about 70 μ m were found. Further, studies to investigate QELBY's energizing effect on germination and early sapling growth in brown chickpea seeds showed at least a 2-3-fold increase in root length and/or formation of shoots. This was seen in seeds bathed in QELBY supernatants or surrounded by QELBY powder outside the vials containing the seeds. This indirect effect was observed whether the QELBY was dry or hydrated.